Retrato da não equidade de gênero nos comitês de bacias hidrográficas do estado do Paraná - Nascimento, Amanda Rodrigues do (2024)
Women play a crucial role in water management for various purposes while taking on fundamental societal responsibilities, including family care and child education. This study aimed to historically analyze gender (in)equality in the watershed committees of Paraná, using a quantitative descriptive approach to characterize these committees, examine the composition of their members, and investigate the social profile of the women who represent them. Data were collected from the institutional pages of the Instituto Água e Terra, the National Water and Basic Sanitation Agency, and through a questionnaire made available to representatives who voluntarily responded. The results reveal a diversity of developmental stages among the committees, reflecting different levels of management and challenges alongside a clear gender disparity. In the eleven watershed committees analyzed, there is evident underrepresentation of women across different segments (Public Authorities, Users, and Civil Society), with only 27% female representation overall and 25% in decisionmaking positions. In committees such as the Piquiri and Paraná II basins, some segments have no female representatives in primary roles, further highlighting the lack of gender equity in these spaces. Another notable finding is that women are more frequently found in substitute roles than primary ones, underscoring the inequality in more influential roles. This disparity emphasizes the urgent need for concrete measures to foster more equitable and inclusive participation across all segments of the watershed committees. The profile of female representatives predominantly comprises married, heterosexual, white, cisgender women aged 50 or older with no children and high incomes. This profile suggests that access to and continuity in these water governance spaces are largely tied to specific socioeconomic and demographic conditions, reflecting a relatively homogeneous and privileged group. This finding underscores the urgency of expanding the representation of more socially vulnerable female groups within watershed committees. In summary, an equitable and democratic composition in watershed committees would enable a broader representation of societal interests, contributing to more inclusive and sustainable decision-making in water resource management.